Ethnobotany of Bhaktapur Municipality - Karmacharya, Siddhi Bir; Shrestha, Anju (Bagiswori Journal, 2019)
The indigenous communities have their unique knowledge about plant wealth to use the plant resources to fulfill their different requirements of medicine food, fodder, fuel wood, timber, house hold equipments, rituals, fencing, roof thatching, manure, rope, animal bedding, poison and more. The objective of the study is to analyze and discuss the plants used by the people ethnically in Bhaktapur Municipality. The 213 species of plants with 72 families with some unknown families were identified and documented from Bhaktapur Municipality. Out of them, 154 species of plants were cultivated 48 were wild and 13 were both cultivated and wild. They included 76 species of medicinal plants with their used parts and diseases cured; 73 species were edible; 64 were species ornamental; 70 species with had miscellaneous uses such as fiber, color, fire wood, timber, fencing, roof thatching, spices, vegetable, oil, food, pulse and poisoning are documented in this study. The result showed that the people had good knowledge on different uses of plant resources but this knowledge was gradually declining. So, it was felt necessary to be documented, preserved, promoted and disseminated.